Pengaruh Bimbingan Belajar Orang tua Terhadap Prestasi Belajar Siswa SD Negeri 1 Erorejo Wadaslintang - Ari Puji Ningsih; Vava Imam Agus Faisal; Apik Anitasari Intan Saputri (DAS Institute, 2024)
This research aims to: 1) To determine the ability of parents to improve students' learning achievement at SD Negeri 1 Erorejo 2) To find out the influence of parental tutoring on students' learning achievement at SD Negeri 1 Erorejo 3) To find out the supporting and inhibiting factors for improving learning achievement Students at SD Negeri 1 Erorejo. This thesis uses a quantitative approach where the type of research is correlational. Data collection techniques use questionnaires, documentation and interviews. Then, data sources were obtained from primary data and secondary data (direct data from the field, books, previous theses, articles and internet sites). Meanwhile, the data analysis technique used is simple regression analysis which is used to predict the extent of the value of the dependent variable and the independent variable. The research results show that: 1) Parental Tutoring at SD Negeri 1 Erorejo Wadaslintang is in the medium category with a percentage of 59.7%. This shows that in the learning process teachers and parents have not implemented learning guidance optimally. 2) The learning achievement of students at SD Negeri 1 Erorejo Wadaslintang is in the medium category, with a percentage of 25%, indicating that student tutoring is still lacking in learning due to teachers or parents not being able to implement the basic aspects of teaching optimally. 3) The influence of parental learning guidance on student achievement at SD Negeri 1 Erorejo Wadaslintang shows a correlation of 0.613, indicating a moderate correlation. From the results of calculations using the interpretation of the r value, it can be concluded that the level of relationship between the influence of parental tutoring on student learning achievement can be said to be strong because the coefficient interval is 0.60 – 0,799. From the hypothesis calculation, the result obtained is 6.493, which is greater than the table of 0.235, indicating that there is a significant influence between parental tutoring on student learning achievement.